2012
DOI: 10.3389/fmicb.2012.00094
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnology and Pasta-Making: Lactic Acid Bacteria as a New Driver of Innovation

Abstract: Cereals-derived foods represent a key constituent in the diet of many populations. In particular, pasta is consumed in large quantities throughout the world in reason of its nutritive importance, containing significant amounts of complex carbohydrates, proteins, B-vitamins, and iron. Lactic acid bacteria (LAB) are a heterogeneous group of bacteria that play a key role in the production of fermented foods and beverages with high relevance for human and animal health. A wide literature testifies the multifaceted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 60 publications
(93 reference statements)
0
22
0
Order By: Relevance
“…In future, strains isolated from idli and currently identified B‐vitamin producers could be subjected and explored with the vitamin overproduction strategies (genetically or chemically induced with roseoflavin) that has been successfully demonstrated in bread and pasta (Capozzi et al . , ) for in situ B‐vitamin enrichment in idli batter. Thus, bioprocessing of idli batter with microbial starters would increase the nutritional value and the quality (Sridevi et al .…”
Section: Discussionmentioning
confidence: 99%
“…In future, strains isolated from idli and currently identified B‐vitamin producers could be subjected and explored with the vitamin overproduction strategies (genetically or chemically induced with roseoflavin) that has been successfully demonstrated in bread and pasta (Capozzi et al . , ) for in situ B‐vitamin enrichment in idli batter. Thus, bioprocessing of idli batter with microbial starters would increase the nutritional value and the quality (Sridevi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Such a fermentation process is due to the presence of yeasts and of bacteria (especially lactic acid bacteria, LAB) that naturally contaminate the flour. Leavening (yeasts and LAB), acidification (LAB) and flavor formation (LAB and yeasts) result in a fermented dough called sourdough . In the industrial food production, the necessary amount of selected strains (starter cultures) added to a raw material to accelerate and steer a fermentation process is usually used to ensure standardization, consistency, safety and quality of the final product .…”
Section: Introductionmentioning
confidence: 99%
“…Leavening (yeasts and LAB), acidification (LAB) and flavor formation (LAB and yeasts) result in a fermented dough called sourdough. [3,4] In the industrial food production, the necessary amount of selected strains (starter cultures) added to a raw material to accelerate and steer a fermentation process is usually used to ensure standardization, consistency, safety and quality of the final product. [5,6] Hence, commercial baker's yeasts [7] started to be used, often in combination with bacterial starters; these leavening agents produce gases, mainly CO 2 , according to the reaction: In this phase, pleasant flavors and aroma precursors (aldehydes, ketones and other volatile organic compounds (VOCs)) take shape, partly due to the biochemical activity of these agents.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, microorganisms may improve or depreciate (i) the safety of the foodstuffs, modulating the content of biological and chemical contaminants (e.g., [22]); (ii) the palatability and the aroma, releasing volatile organic compounds and influencing the taste and the texture (e.g., [23]); (iii) the nutritional quality, modifying the quantity of macro-and micro-nutrients and their digestibility and bioavailability (e.g., [24]); (iv) the presence (in quality and quantity) of biological and/or chemical entities susceptible to maximize the consumer health (out of the benefits associated to the nutritional contribute) (e.g., [1,25]). Other case studies are reported in Table 2 to better exemplify how microbes can affect the global quality of fermented foods and beverages, encompassing applications such as toxic compound degradation, texturizing properties, bio-fortifications, and addition of functional ingredients [26][27][28][29]. Table 2.…”
Section: Major Groups Global Fermented Foodsmentioning
confidence: 99%